Measurement and analysis of municipal fields of the Region of Hodna, (M’sila province, Algeria) - Abbas, Saliha (Technium Social Sciences Journal, 2023)
The administrative meshes constitutes an architecture put in place by a State to exercise its powers on the national territory, If the administrative mesh is characterized by limits and an extent, its geographical study requires to be interested as much in the container as in the content, The administrative network is a simple mesh placed on a space, the administrative network can become a geographical object in itself, when it is recognized and appropriated by the population, The engineering of divisions is a first approach to understanding the formation of administrative meshes, the size and design of the stitches are one aspect of this, This study attempts to shed light on the principles of administrative division of Algeria in general and the municipal network in the province of M’sila in particular, and to characterize the main consecutive imbalances, The degree of spatial efficiency is assessed using the measurement and analysis of the shapes of the municipalities by the application of three indexes, the shape index, the polygons of Thiessen and Reilly’s Law of retail gravitation, In the last We suggest some orientations for an administrative reorganization in order to achieve a better balance.